Penyelenggaraan Festival Anak Sholeh di Lingkungan Damme, Kelurahan Patte’ne, Kecamatan Polombangkeng Selatan, Kabupaten Takalar - Santih Anggereni; Zulkarnain Sultan; Tamsil; Annisa Tul Muazirah; Ramlahsari; Muh Asfar Lamma; Muh Nur Wahyu H; Nur Fatimah Azzahrah; Astri Zahri Miftahuljannah R; Nur Indah Salsabilah; et al. (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2023)
The pious children festival is one of the joint work programs organized by KKN Students at the Alauddin State Islamic University Makassar (UINAM) in the Patte’ne Village. The purpose of holding this pious children’s festival program is; (1) to increase enthusiasm for learning islam; (2) developing interests and talents in the field of religion; (3) to develop the level of artistic creativity; and (4) to increase the self-confidence of children in the Patte’ne Village. The implementation of the pious children’s festival program consists of 4 activities, namely, short letter memorization competitions, daily prayer memorization competitions, call to prayer competitions, and Islamic fashion show competitions. The implementation method applied to the pious children’s festival program uses debriefing, training, and practice methods. The result of this pious children’s festival program is that children in the Patte’ne Village are more enthusiastic about learning the Islamic religion, then the children in the Patte’ne Village are also more daring to show their talents and their sel-confidence has increased after participating in the pious children’s festival program. This is evidenced by several boys in the Patte’ne Village who initially did not dare to do Islamic fashion shows but after training, many boys took part in the pious child festival activities.